1974
DOI: 10.1128/iai.10.5.985-990.1974
|View full text |Cite
|
Sign up to set email alerts
|

Some Immunochemical Properties of Dextransucrase and Invertase from Streptococcus mutans

Abstract: Dextransucrase and invertase of some strains of Streptococcus mutans were examined by immunodiffusion with antisera against enzymes purified from strain HS-6 (Bratthall's serotype a). Both antisera cross-reacted with crude enzyme preparations from the other serotype a (strains HS-1 and AHT) and d organisms (strains KIR, OMZ176, and OMZ65) but not with those from serotype b (strains FA-1 and BHT) or c organisms (strains GS-5, Ingbritt, and NCTC 10449). Based upon the antiserum used, the orders of antigenic simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
23
0

Year Published

1976
1976
1983
1983

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 22 publications
3
23
0
Order By: Relevance
“…During many studies designed to measure antibodies directed against S. mutans dextransucrase preparations, it has been consistently ob-served that control and sometimes immune sera caused an elevation rather than an inhibition of glucan production from sucrose (4,9,10,20,22,27). Based on studies with sera and oral fluids from rats, Burckhardt and Guggenheim (4) proposed that there were sites on the S. mutans dextransucrase which could interact with molecules in the fluids and enhance glucan production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During many studies designed to measure antibodies directed against S. mutans dextransucrase preparations, it has been consistently ob-served that control and sometimes immune sera caused an elevation rather than an inhibition of glucan production from sucrose (4,9,10,20,22,27). Based on studies with sera and oral fluids from rats, Burckhardt and Guggenheim (4) proposed that there were sites on the S. mutans dextransucrase which could interact with molecules in the fluids and enhance glucan production.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced glucan production results from an increase in the velocity of polymerization of the glucosyl moiety of sucrose due to a high affinity interaction between phospholipid and a site on the enzyme which appears to be distinct from either the glucosyl donor or glucosyl acceptor sites. We have proposed (28) that the observed stimulation of dextransucrase activity by control and/or immune sera and oral fluids from monkeys (27), rabbits (9,10,20,22), and rats (4) is due to the presence of stimulatory phospholipids in these materials.…”
mentioning
confidence: 99%
“…Antibodies against GTase(s) inhibit enzyme activity (1,6,7,9,10,21,23,35) and result in the reduction of experimental caries of S. mutans in rats (37). 5. mutans has been classified into seven serotypes (3,14,15,31) of which immunological specificity is based on the cell wall polysaccharide (12,17,22,23,26,27,40).…”
mentioning
confidence: 99%
“…Initial studies with whole cell antisera and antiserum to crude enzyme preparations have reported inhibition of total or cell-associated glucan synthesis and inhibition of cell adher- ence to wire and glass surfaces (6,10,22,27). Fukui et al have prepared an antiserum to a highly purified a-1,6-glucan:n-fructose 2-glucosyltransferase and utilized it to examine crossreactions among the enzymes synthesizing soluble glucans from the various serotypes of S. mutans (9). The present report describes an antiserum specific for the glucosyltransferases which synthesize insoluble glucans.…”
mentioning
confidence: 99%